2010
DOI: 10.1007/s00423-010-0660-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary closure versus T-tube drainage after common bile duct exploration for choledocholithiasis

Abstract: The primary closure might be as effective as T-tube drainage after choledochotomy in the prevention of the development of post-operative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 28 publications
5
25
0
1
Order By: Relevance
“…Because these differences in defining outcome parameters (i.e., biliary complications) could lead to heterogeneity, we performed another synthesis of data regarding biliary complications without a combination of retained stones. The results suggested that primary closure has a significantly lower biliary complication rate, which is consistent with another metaanalysis [33] that evaluated the safety and effectiveness of primary closure for CBDE.…”
Section: Discussionsupporting
confidence: 89%
“…Because these differences in defining outcome parameters (i.e., biliary complications) could lead to heterogeneity, we performed another synthesis of data regarding biliary complications without a combination of retained stones. The results suggested that primary closure has a significantly lower biliary complication rate, which is consistent with another metaanalysis [33] that evaluated the safety and effectiveness of primary closure for CBDE.…”
Section: Discussionsupporting
confidence: 89%
“…[14] However, this method is not only more difficult, but also prone to bile leakage, bleeding, and a series of complications. [1416] T-tube drainage could lead to excessive bile and electrolyte loss, affect the patient's recovery, prolong hospital stay, and increase treatment costs. [17,18] The use of minimally invasive techniques could reduce surgical trauma, hasten recovery, and reduce length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…To date four meta-analyses have been performed to compare the results of PDC with those of TTD [21,[29][30][31]. The most complete pooled analysis, performed by Yin et al [31], enrolled twelve studies (three randomized controlled trials and nine retrospective cohort studies) comparing PDC, with or without BD insertion, and TTD.…”
mentioning
confidence: 98%